Involvement of ACE2 in the intestinal transport of amino acids: Possible health and nutritional consequences in altered expression (Bangladesh Journal of Medical Science, 2023)
Background:Absorption of neutral amino acids across the intestinal cells is mediated by the broad neutral amino acid transporter B0AT1. Intestinal expression of B0AT1 depends on the coexistence with the membrane-attached angiotensin-converting enzyme 2 (ACE2) which binds to the B0AT1 or the sodium-dependent imino-acid transporter 1 (SIT1) in the intestinal epithelial cells.Objectives:The objective of this article is to provide an overview of the involvement of ACE2 in the transport of amino acids from the intestinal lumen and possible harmful effects on health and nutrition due to altered ACE2 expression.Methods: PubMed, Scopus, and Google Scholar were searched using the keywords ACE2 paired with intestinal and gut B0AT1, SIT1, amino acid transport or absorption, health, and nutrition. Expression of B0AT1 in the intestine was completely absent in ACE2 knockout mice. Lack of ACE2 and B0AT1 expression lead to low plasma and muscle tryptophan, niacin deficiency, decreased intestinal antimicrobial peptide, and increased susceptibility to inflammatory bowel disease in animal models.Results: Expression of ACE2 in the small intestine and its association with amino acid transporters play a crucial role in the absorption of amino acids, maintenance of structural and functional gut integrity and overall health and nutrition status of an individual.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 729-733